2018 IEEE 48th International Symposium on Multiple-Valued Logic (ISMVL) 2018
DOI: 10.1109/ismvl.2018.00039
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hardware Realization of Convolutional Neural Networks Using Intra-Kernel Regular Pruning

Abstract: The recent trend toward increasingly deep convolutional neural networks (CNNs) leads to a higher demand of computational power and memory storage. Consequently, the deployment of CNNs in hardware has become more challenging. In this paper, we propose an Intra-Kernel Regular (IKR) pruning scheme to reduce the size and computational complexity of the CNNs by removing redundant weights at a fine-grained level. Unlike other pruning methods such as Fine-Grained pruning, IKR pruning maintains regular kernel structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The majority of works in this direction apply a pretraining-pruning-retraining flow, which is not compatible with the trainingon-the-edge paradigm. According to the adopted sparsity scheme, those works can be categorized as unstructured [16,1], structured [24,2,25,26,17,3,27,28,29,30,31,18,32,33], and fine-grained structured [19,34,35,36,37,38,39,40,41] including the pattern-based and block-based ones. Detailed discussion about these sparsity schemes is provided in Appendix A.…”
Section: Sparsity Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of works in this direction apply a pretraining-pruning-retraining flow, which is not compatible with the trainingon-the-edge paradigm. According to the adopted sparsity scheme, those works can be categorized as unstructured [16,1], structured [24,2,25,26,17,3,27,28,29,30,31,18,32,33], and fine-grained structured [19,34,35,36,37,38,39,40,41] including the pattern-based and block-based ones. Detailed discussion about these sparsity schemes is provided in Appendix A.…”
Section: Sparsity Schemementioning
confidence: 99%
“…Furthermore, as with inference acceleration, we find that sparse training closely relates to the adopted sparsity scheme such as unstructured [16], structured [17,18], or fine-grained structured [19] scheme, which can result in varying accuracy, training speed, and memory footprint performance for sparse training. With our effective MEST framework, this paper systematically investigates the sparse training problem with respect to the sparsity schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, iterative pruning was used to add multiple tasks to a single network by Mallya and Lazebnik [29]. IKP pruning scheme was advanced by Yang et al [30] for removing redundant weights at a fine-grained level and showed good performance in hardware accelerator. To prune the deep models for object detection, Ghosh et al [31] analyzed the pruning approach about the detection networks and utilized the pruning technique based on agglomerative clustering for the feature extractor and mutual information for the detector.…”
Section: Related Workmentioning
confidence: 99%
“…Complementary to those mobile inference acceleration approaches, DNN model compression techniques provide another possibility to efficient on-device inference. Two main-stream model compression techniques are weight pruning [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36] and weight quantization [37], [38], [39], [40], [41]. Weight pruning enjoys the great flexibility of various DNN weight sparsity schemes and has achieved very high pruning rate and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the pattern-based weight pruning techniques [34], [35] provide a novel weight sparsity scheme, i.e., the fine-grained structured sparsity. It can be considered as enabling a certain level of flexibility in the previous (coarsegrained) structured sparsity, thus simultaneously boosting the accuracy of the structured sparsity and facilitating realtime on-device inference.…”
Section: Introductionmentioning
confidence: 99%